Local politics, political institutions, and public resource allocation - Palaniswamy, Nethra; Krishnan, Nandini (International Food Policy Research Institute, 2008)
This paper examines how political institutions and local power structures interact with and influence local public resource allocation in the Indian state of Karnataka. We use data from 80 village councils and 225 villages to examine how this local political economy influences the allocation of public resources. Our empirical strategy exploits certain features of a policy that mandates representation for historically disadvantaged groups, including the Scheduled Castes (SC) and Scheduled Tribes (ST), in village councils. These features imply that representation is a nonlinear function of the demographic shares of these groups. Controlling for the latter allows us to identify the role of local power structures through the effect of social identities and the associated relative bargaining powers of different caste groups. We find that the design of political institutions matters to resource allocation. Although a formula-bound allocation of fiscal grants to the village councils was successfully implemented, the within-council allocation governed by a legislative voting process reveals severe targeting failures. Importantly, we find that these targeting failures reflect elements of elite capture. Villages represented by politicians belonging to the SCs and STs get fewer fiscal resources. We also find evidence that villages represented by the politically dominant castes are likely to get more resources. Taken together, these results suggest that the capture of decentralized institutions by the local elite skews public resource allocation. The results also suggest that the use of a formula might lead to a more equitable intervillage allocation of public resources.